Pre-service Teachers’ Perception on the Reflective Teaching Practices in Micro Teaching Class - Supriadi Torro; La Sunra; Riskawati Riskawati (Journal of Educational Science and Technology (EST), 2021)
This study was a descriptive quantitative analysis aimed to find out the student teachers’ perception of the Reflective teaching practice at pre-instructional, instructional and post instructional stage in EFL micro teaching class. The population in this research was the English language education students who have attended Micro teaching courses. 108 students participated in this research by completing questionnaire. The data analysis technique used in this research is descriptive analysis using SPSS program for Windows version 17.0. The statistical analysis showed that the Mean score was 201.16, Median 199, Mode 184, and Standard deviation 16.923 from the total score of 21,275. The pre-service teachers’ perception on the reflective teaching practice at pre instructional stage and post-instructional stage was in very good category whereas their perception at the instructional stage was in the good category. This is to say, the pre-service teachers perceived that reflective teaching practice was carried out well in EFL micro teaching class at UNM.